THE USE OF DIGITAL INTERACTIVE MIND MAP TO ENHANCE STUDENTS' CONCEPT MASTERY AND CREATIVITY IN LEARNING EXCRETORY SYSTEM - Anis Nuur Faaizah, - (2020)
Students were raised in different ways in this called "digital natives" era that very familiar with technology. Students need to have the skills that can guarantee their competitiveness in the globalization age, and the skills needed are called 21st century skills. 21st century teacher should be ready to embrace the technology in learning process; one of the teaching media that can be used is Digital Interactive Mind Map. To enhance the quality of education, concept mastery and creativity is very important to be involved as elements of learning outcomes. Thus, this research was aimed to investigate the use of Digital Interactive Mind Map to enhance students' concept mastery and the effects towards creativity in learning excretory system. The method which was used in this research is pre-experiment with one group pretest-posttest design. The population in this research was one class of students in 8th grade in Private Junior High School in Bandung. The sampling technique was Convenience Sampling. The number of participants includes 18 male students. The result shows that the students' concept mastery improved as shown N-gain score is above 0.80 which categorized as high development. For students' creativity gained different result in every indicators but have the same interpretation which is "Good" with the results above 75%. Students' creativity for fluency indicator shows 81% of result, flexibility indicator is 79%, originality indicator is 77%, and elaboration shows 80% of result. Overall, the students show good impression to the implementation of digital interactive mind map in learning about excretory system. Based on the result, it significantly affects to students' concept mastery and creativity in learning excretory system.